2005
DOI: 10.1073/pnas.0509148102
|View full text |Cite
|
Sign up to set email alerts
|

Developmental checkpoints of the basophil/mast cell lineages in adult murine hematopoiesis

Abstract: Basophils and mast cells, which are selectively endowed with the high-affinity IgE receptor and mediate a range of adaptive and innate immune responses, have an unknown developmental relationship. Here, by evaluating the expression of the ␤7 integrin, a molecule that is required for selective homing of mast cell progenitors (MCPs) to the periphery, we identified bipotent progenitors that are capable of differentiating into either cell type in the mouse spleen. These basophil͞mast cell progenitors (BMCPs) gave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
353
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(375 citation statements)
references
References 39 publications
18
353
1
3
Order By: Relevance
“…1C), with Ct between 24 and 30. In contrast, C/EBPa that controls basophil lineage commitment [26] was faintly expressed by adipose-derived CFC (Ct around 34). Finally, murine mast cell-specific serine protease (pmMCP)-5 mRNA was highly expressed (Ct around 22) in contrast to mMCP-1 (Ct around 31) in adipose-derived CFC and peritoneal cell-derived mast cells (Fig.…”
Section: Adipose Tissue Harbors Mast Cell Progenitors and Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…1C), with Ct between 24 and 30. In contrast, C/EBPa that controls basophil lineage commitment [26] was faintly expressed by adipose-derived CFC (Ct around 34). Finally, murine mast cell-specific serine protease (pmMCP)-5 mRNA was highly expressed (Ct around 22) in contrast to mMCP-1 (Ct around 31) in adipose-derived CFC and peritoneal cell-derived mast cells (Fig.…”
Section: Adipose Tissue Harbors Mast Cell Progenitors and Precursorsmentioning
confidence: 99%
“…First, adipose-derived CFCs were amplified in liquid medium containing IL-3 and SCF [26] giving rise to a homogeneous population of granular cells showing the same morphology as mast cells obtained in methylcellulose (MGG staining, Supporting Information Fig. 2).…”
Section: Adipose-derived Hematopoietic Restricted Progenitors Differementioning
confidence: 99%
“…In all 3 instances, the markers used for depletion are also expressed on the mast cell, the committed mast cell progenitor, and/or the common basophil-mast cell progenitor identified in the spleen of C57BL/6 mice by Arinobu et al 6 Although none of the authors noted a decrease in the mature mast cell number identified in the peritoneal cavity of mice, these cells represent a mature end-stage cell that may not be affected in the limited time frame of these treatments. Nonetheless, this consideration does not diminish other aspects of the study, which demonstrated a life span of basophiles of only about 60 hours and the increased production of these cells in the bone marrow following helminth infection.…”
Section: The Expanding Universe Of the Basophil ---------------------mentioning
confidence: 99%
“…This latter finding is consistent with those of Arinobu et al who, following infection with the helminth, Trichinella spiralis, also noted increased basophil production by the bone marrow and increased numbers of the common basophil-mast cell progenitor in the spleen. 6 Importantly, Ohnmacht and Voehringer then addressed whether the increased numbers associated with TH-2 inflammation was the result of increased production, increased survival, or both. The increased survival as a consequence of the cytokines generated by TH-2 inflammation, particularly IL-3, has been shown in vitro using human basophils 7 and was recently further studied by Didichenko et al, who found this is mediated by IL-3 activation of PIM-1.…”
Section: The Expanding Universe Of the Basophil ---------------------mentioning
confidence: 99%
See 1 more Smart Citation